Electrophysical characteristics of nanodimensional cobalte-cuprate-manganite LaNa2CoCuMnO6 and nickelite-cuprate-manganite LaNa2NiCuMnO6 - Ш.Б. Касенова; Ж.И. Сагинтаева; Б.К. Касенов; Е.Е. Куанышбеков; Ж.С. Бектурганов; А.К. Зейниденов (Қарағанды университетінің хабаршысы. Физика сериясы)
The temperature dependences of the electric capacity, dielectric constant and electrical resistance of cobaltecuprate-manganite of lanthanum and sodium of LaNa2CoCuMnO6 and nickelite-cuprate-manganite of lanthanum and sodium of LaNa2NiCuMnO6 were investigated on the LCR-800 serial device (manufactured by Taiwan) at the operating frequencies of 1 kHz, 5 kHz, and 10 kHz in interval of 293–483 K through 10 K continuously in dry air. It was determined that LaNa2CoCuMnO6 in interval of 293–483 K shows the semiconductor conductivity. A band gap (D Е) is 0.54eV. The compound has the high values of the dielectric constant, which are equal 2.17×106 (1 kHz), 2.31×105 (5 kHz), 8.22×104 (10 kHz) at 293 K and 8.49×108 (5 kHz), 7.87×107 (10 kHz) at 483 K. LaNa2NiCuMnO6 in interval of 293–483 K demonstrates the semiconductor conductivity (D Е = 0.48 eV), at 433–443 K — the metallic conductivity and at 453–483 K — the semiconductor conductivity (D Е = 2.33 eV).The values of the dielectric constant are 4.97×103 (1 kHz), 9.2×102 (5 kHz), 5.1×101 (10 kHz) at 293 K and 1.02×106 (1 kHz), 1.98×105 (5 kHz) and 9.76×104 (10 kHz) at 483 K. The compounds can be classified as the narrow-band gap semiconductors and they are of interest for the semiconductor and microcapacitor technologies.